Behavioral biases in pension fund trustees' decision making. (18th June 2019) - Weiss-Cohen, Leonardo; Ayton, Peter; Clacher, Iain; Thoma, Volker
Abstract : Purpose: Behavioral finance research has almost exclusively investigated the decision making of lay individuals, mostly ignoring more sophisticated institutional investors. The purpose of this paper is to better understand the relatively unexplored field of investment decisions made by pension fund trustees, an important subset of institutional investors, and identify future avenues of further exploration. Design/methodology/approach: This paper starts by setting out the landscape in which pension fund trustees operate and make their decisions, followed by a literature review of the extant behavioral finance research applicable to similar situations. Findings: Despite receiving training and accumulating experience in financial markets, these are limited and sparse; therefore, pension fund trustees are unlikely to be immune from behavioral biases. Trustees make decisions in groups, are heavily reliant on advice and make decisions on behalf of others. Research in those areas has uncovered many inefficiencies. It is still unknown how this specific context can affect the psychological effects on their decisions. Research limitations/implications: Given how much influence trustees' decisions have on asset allocation and by extension in financial markets, this is a surprising state of affairs. Research in behavioral finance has had a marked influence on policy in the past and so we anticipate that exploring the decisions made within pension funds may have wide ramifications for the industry. Originality/value: As far as the authors are aware, no behavioral research has empirically tested pension fund trustees' decisions to investigate how the combination of group decisions, advice and surrogacy influence their decisions and, ultimately, the sustainability of our pensions.